PAI Teachers' Efforts in Fostering Blink's Style of Dress in Indonesia - Nursakti, Muhammad Saman; Slamet, Ubaidillah Al-Ghifary; Widyastri, Sri (Sahabat Publikasi, 2024)
This study aims to analyze and find out the right efforts for PAI teachers in maintaining the dressing style of students, especially students who idolize the Black Pink band which is usually called Blink. This study used descriptive qualitative method. Using primary sources obtained from interviews with PAI teachers, school documents, and interviews with students who idolize Black Pink. In addition, researchers also get secondary sources that researchers get from the internet, books, and the latest journals. Based on the results of research that has been obtained, it shows that the right PAI teacher's efforts in maintaining Blink's dressing style at SMAN 06 Bekasi are to provide religious advice and advise students to be wise in using social media, provide examples to students, provide punishment if they violate with punishment that does not hurt, collaborate with the entire academic community, and parents. As well as creating a good environment for students, by introducing Islamic heroes and instilling moral values to students.